METODE DAKWAH BIL-LISAN IMUM GAMPONG DALAM PEMBINAAN ETIKA REMAJA (Studi di Desa Ulee Jalan Kecamatan Banda Sakti Kota Lhokseumawe) - Aminullah, Muhammad; Muttaqien, Muttaqien; Halimatussa`diah, Halimatussa`diah; Oktavira, Fadhila (Liwaul Dakwah: Jurnal Kajian Dakwah dan Masyarakat Islam, 2021)
This study describes the role of imum gampong in carrying out the bil oral da'wah method in ethical development for adolescents. Considering that adolescence is a period of transition, the entry of foreign cultures is enough to influence the formation of adolescent character. If teenagers are not guided and directed, it is not impossible that teenagers will be dragged into bad culture and associations. This study needs to find out about the method of preaching the bil-lisan of Imum Gampong Ulee Jalan Banda Sakti District, Lhokseumawe City, the supporting and inhibiting factors of the billisan da'wah method, Imum Gampong Ulee Street, Banda Sakti District, Lhokseumawe City. The research method used is qualitative research, the nature of descriptive research and sociological research approach. Data collection techniques through observation, interviews and documentation techniques. Based on the results of the study, it can be found that the Da'wah bil-lisan method of Imum Gampong in fostering the ethics of teenagers in Ulee Jalan Village is carried out through routine recitations every Tuesday and Friday night which is provided with special recitation places, reprimands to teenagers who make mistakes and religious lectures that are held on Sundays. Islamic holidays. While the supporting factors for the Imum Gampong bil-lisan da'wah method in fostering adolescent ethics in Ulee Jalan Village are the availability of learning places for routine recitations and books that become learning references, support from all levels of society and awareness of each teenager. And the inhibiting factors are the availability of rudimentary reference books, lazy nature because they are busy with activities during the day and the less harmonious relationship between teenagers and teachers.